EVALUASI TEBAL PERKERASAN LENTUR PADA PROYEK PEMBANGUNAN JALAN PELABUHAN TELUK TAPANG – BUNGA TANJUNG KABUPATEN PASAMAN BARAT - Anton Andre; Ishak Ishak; Helga Yermadona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
AbstractWest Pasaman Regency is one of the regencies in West Sumatra, with an area of 3,864.02 km2 with a population of 365,129 people West Pasaman Regency has an administrative area with the northern border bordering mandailing Natal Regency of North Sumatra Province, the east borders Pasaman Regency, the south borders Pasaman Regency and Agam Regency of West Sumatra Province, The west borders the Indonesian Ocean. The purpose of this study was to compare the two methods on the thickness of the bending pavement using the method from AASHTO 1993 and the Bina Marga Road Pavement Design Manual Method 2017. Evaluation of the thick bending pavement using the Bina Marga Road Pavement Design Manual method 2017 and the AASHTO 1993 method is further grouped according to identification and problems, so that effective and directed solution analysis can be obtained. Thick bending pavement with bina marga method 2017 obtained the thickness of the bottom foundation 30 cm, Ac-Base 8 cm, AC-BC 6 cm, and AC-WC 4 cm. The thickness of the bending pavement with the AASHTO method 1993 obtained the thickness of the foundation D1 = 15 cm, D2 = 10 cm, and D3 by 10 cm. Differences in the results of the thick design of pavement obtained from the Bina Marga method 2017 and the AASHTO method 1993 are due to differences in concepts, parameters and design procedures in both methods. The design concept in Bina Marga 2017 is mechanistic empirical, while in AASHTO 1993 in the form of empirical methods.Key words: Flexible Pavement, Bina Marga 2017, AASHTO 1993.